Effect of parboiling on biochemical and functional properties of little millet (panicumsumatrense L.) - A.RENI; S.GOBIKRISHNAN (International Journal of Pharma and Bio Sciences, 2017)
The purpose of this study was to determine the effect of parboiling process in biochemical and functional properties of the little millet (Panicumsumatrense L.).The biochemical and functional properties of parboiled and un-parboiled little millet was analyzed and compared. The obtained results showed that after parboiling process the total carbohydrate and crude fibre content was decreased from 62.50% to 45.78% and 1.47% to 0.97% was observed for the little millet. There was an increased ash content, calcium content, antioxidant value and colour value was observed for little millet after parboiling process from 5.566 to 6.061; 67.18mg/100g to 99.38mg/100g;59.9µg/g to 206.42µg/g and L*- 95.38, a*- 2.46, b*- 6.23 to L*-100.93, a*-1.66, b*-0.97, respectively. The functional properties such as Water Absorption Capacity (WAC), Water Solubility Index (WSI), Swelling Power (SP) were also increased in the little millet from 1.62 to 1.772;4.8 to 6.4;1.36 to 3.32, respectively after parboiling process. This investigation concluded that parboiled little millets contained great level of nutrition, biochemical and functional properties when compared to the un-parboiled little millet.